2009
DOI: 10.1366/000370209787944325
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ultraviolet Resonance Raman Spectroscopy in the Analysis of Ionizing-Radiation-Induced Damage in DNA

Abstract: Ultraviolet resonance Raman spectroscopy (UVRRS) was used to determine damage done in both calf-thymus DNA (CT-DNA) and a short stranded DNA oligomer (SS-DNA) due to ionizing radiation from a medical (60)Co radiation therapy unit used in the treatment of cancer. Spectra were acquired at incident UV wavelengths of 248, 257, and 264 nm in order to utilize the differences in UVRR cross-sections of the bases with wavelength. Through the analysis of difference spectra between irradiated and unirradiated DNA at each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Spectroscopic techniques are powerful tools for detecting and studying DNA lesions. Their chemical sensitivity makes them the most accurate tool for the detection of even small structural changes [32]. Moreover, techniques based on the interaction of electromagnetic field with chemical bonds enables us to receive the fingerprint spectra of the investigated molecules, allowing for the simultaneous detection of various functional groups typical for the investigated sample.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic techniques are powerful tools for detecting and studying DNA lesions. Their chemical sensitivity makes them the most accurate tool for the detection of even small structural changes [32]. Moreover, techniques based on the interaction of electromagnetic field with chemical bonds enables us to receive the fingerprint spectra of the investigated molecules, allowing for the simultaneous detection of various functional groups typical for the investigated sample.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have applied RS for cellular biochemical analysis of apoptosis (Verrier et al 2004, Zoladek et al 2011, necrosis (Kunapareddy et al 2008), cell death (Notingher et al 2003), non-proliferation (Short et al 2005) and cell cycle (Swain et al 2008, Matthews et al 2010. In radiobiological applications, RS has detected molecular alterations in irradiated aqueous DNA (Sailer et al 1996, Shaw andJirasek 2009), sodium hyaluronate (Synytsya et al 2011), biological membranes (Verma 1986, Verma and Rastogi 1990, Verma and Sonwalkar 1991, Verma et al 1993, Sailer et al 1997, and skin and muscle tissues (Lakshmi et al 2002, Synytsya et al 2004. A recent clinical RS study discriminated between responding and non-responding cervical cancers post-irradiation (Vidyasagar et al 2008), yet made no conclusions regarding the differences in the biochemical composition between tissues or the molecular basis for RS discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a DUV resonant Raman spectrum varies with microenvironment of nucleotide bases in a nucleic acid . The spectrum was used for analyzing nucleic acid conformation, such as supercoiling, folding, and melting …”
Section: Resonant Raman Scattering For Imaging and Analysismentioning
confidence: 99%